Marriage Is Scary Trend in the Perspective of Islamic Law and Positive Law - Al Mafaz, Fina; Arfan, Abbas; Fakhruddin, Fakhruddin (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
Indonesia is experiencing a decline in marriage rates along with a high divorce rate. At the same time, a trend emerged on social media called Marriage Is Scary. The Marriage Is Scary trend expresses the young generation's fear of marriage. This research aims to analyze the Marriage Is Scary phenomenon from the perspective of Islamic law and positive law in Indonesia. The method used is normative legal research with a conceptual and statutory approach. The results of this study show that marriage in Islam has a variety of laws, which can be sunnah, obligatory, makruh, haram, and mubah. The young generation's fear of marriage, when related to the law of marriage in Islam, must first be seen as the cause of this fear. In essence, Islam emphasizes the readiness to carry out marriage from various aspects. In terms of positive law, Indonesia has multiple regulations, such as the Marriage Law, the Law on the Elimination of Domestic Violence, and the Marriage Guidance Program as a form of the government's commitment to creating an environment conducive to healthy and ideal marriages, as well as an answer to the Marriage Is Scary trend.